Electrochemical analysis of sildenafil citrate on electrode modified with nitrogen and sulfur-doped reduced graphene oxide - Ngô, Thị Thanh Xuân; Lê, Đức Anh; Nguyễn, Quang Mẫn (Hue University Journal of Science: Natural Science, 2025)
In this study, nitrogen and sulfur-doped reduced graphene oxide (rGO(N.S)) was prepared with the hydrothermal method. The rGO(N.S) material was characterized with X-ray diffraction and Raman spectroscopy. A glassy carbon electrode was modified with the rGO(N.S) material to develop a novel electrochemical sensor for analysing sildenafil citrate (SDC). The electrochemical parameters of the differential pulse voltammetry technique such as accumulation potential, accumulation time, pulse amplitude, and potential step were investigated and optimized, showing a relatively low detection limit of SDC.